General guidelines for the design of an indicator of the level of industrial activity - Ortiz, Hernán (Estudios de Economía, 2016)
The interest in the monthly, indexes of industrial production is related to the large volume and the cyclical importance of industrial output. Around the 20th of each month, argentine agencies issue estimates of the industrial out put for the previous month. This methodological paper describes the possible sources of data, the concepts and classifications used, the different measurements and the process of estimation. It is suggested that the industrial production index can be used in conjunction with other indicators, such as those coming from qualitative surveys, so as to reach a wider understanding of the evolution of industrial output.